Laparoscopic Removal of an Intrauterine Contraceptive Device Migrated into the Bladder: A Case Report - Campobasso, Davide; Ciuffreda, Matteo; Maestroni, Umberto; Dinale, Francesco; Frattini, Antonio; Ferretti, Stefania (Urology Journal, 2014)